Ismail Sidqi and his Economic Activity in Egypt 1914-1934 - Abdul-rahman, Mazin Mahdi (Al-Adab Journal, 2015)
Ismael Sadeki is considered as one of the important historical figures who have passed in the history of Egypt, and that has affected the modern history of the country, positively or negatively. In spite of his reputation that made him unnamable by the Egyptian people. Some regarded him as a dictator that does not care for human rights. His reputation in the economy in his role in the Egyptian economy was something full of sufficiency in finance and administration. His era was full of achievements finance and administration. He was known in his sufficiency since early age which he became in 1914. Then, he presided over the Trade and Industry Committee in 1916, and then he presided over the Egyptian economic council and in the Industries Union in 1922 in addition to his cooperation with the foreigners